Histórias não contadas : acolhimento institucional de recém-nascidos de mulheres usuárias de drogas - Rangel, Gediane Laurett Neves (2018)
Even before leaving the maternity hospitals, the loss of legal custody of newborns by women who use drugs is a reality in Brazil, as registered in other countries (such as the United States and England). In this study we show that the institutional care of these infants – even though under the aegis of the doctrine of whole protection to the child – is influenced by conservative ideologies that historically guide the intervention of the State on poor women and families. This study aims to analyze the institutional care process imposed on newborns of women who use drugs, in the City of Vitória, taking place at the HUCAM Maternity Hospital between 2008 and 2017, in order to reflect on the repercussions for the subjects (women and children) involved. We address here poor, black women, strongly submitted to the ideal standard of good mother, to which they do not correspond. We also show that of the 17 children received in the study period only one was reintegrated to the mother. Eight were adopted and eight were delivered to the care of the extended family. Despite the fact that they are in the Municipal Health and Social Services, most women have never received systematic follow-up. We conclude that the institutional care, defended under the prism of the doctrine of whole protection to the child, does not see that it deprives mothers of affection, relationships and rights. The State, by holding women accountable for their behavior and penalizing them with the loss of their children, does not ensure the social and human rights to which both mother and child would be entitled, and also fails to provide conditions that allow poor mothers who use drugs to remain with their children.